GROUNDWATER ARSENIC DISTRIBUTION IN SOUTH-WESTERN URUGUAY - Manganelli A.; Goso C.; Guerequiz R.; Fernández Turiel J.L.; García Vallès M.; Gimeno D.; Pérez C. (My University, 2007)
This is the first specific information regarding arsenic distribution of groundwater in SW Uruguay. Twenty-eight wells were sampled on the aquifers of Mercedes, Raigón and Chuy in five localities. The pH, specific conductivity and temperature were determined in the field. The hydrochemical characterization (major and trace elements) was carried out by both inductively coupled plasma-optical emission spectrometry and inductively coupled plasma-mass spectrometry. The occurring arsenic concentrations exceed the recommended threshold for drinking water of the World Health Organization (10 μg/l of As) in 22 samples, with more than 50 μg/l of As in two cases. The median, minimum and maximum concentrations were 0.1, 16.9 and 58.0 μg/l of As, respectively. The studied aquifers present a horizontal and a vertical variation of the concentrations as a whole as well as individually. The highest values were observed in the Mercedes Aquifer in the areas near the Uruguay River.
Keywords: ARSENIC; GROUNDWATER; AQUIFER; URUGUAY